Oxidation behaviour of synthetic stainless steel interdiffusion layers. (4th May 2018) - Balinski, K.; Jahns, K.; Schroth, M.; Bursich, S.; Salime, J.; Impey, S.; Chalk, C.; Wübbelmann, J.; Nicholls, J. R.; Krupp, U.
Abstract: The possibility of creating an oxidation-protection layer system composed of Fe, Ni and Cr on top of a plain carbon steel substrate by means of electroplating is investigated within this study. It is shown that by applying an appropriate heat treatment, interdiffusion takes place transforming the individual layers into a gradient structure with stainless-steel-like properties. The layering process combined with the interdiffusion heat treatment allows numerous stainless-steel-like compositions to be produced. The proposed layer-by-layer electrodeposition process is followed by vacuum annealing, where interdiffusion of the various elements causes a redistribution of the phase composition, leading to a gradient corrosion-resistant layer. The samples were vacuum-annealed at 1030 °C for 24 hours and oxidized in air at 700 °C for various time periods afterwards. The respective oxidation behaviour of the interdiffusion layers was characterized by applying analytical SEM to ground and polished cross sections.